The Looming Threat of Burns Epidemic in Pakistan: Challenging Issues and The Way Forward. - Iqbal, Tariq (Journal of Postgraduate Medical Institute, 2024)
Burn injuries represent one of the commonest and most important public health issue developing countries like ours (Pakistan). Following road traffic accidents (RTAs), burns constitute the second commonest cause of cause of accidental deaths. The overall incidence of burn injuries per 100, 000 population is 76.3 for emergency visits, 17.0 for hospitalization and 0.3 for emergency deaths. Our country is face with a dual challenge. On one hand have a disconcertingly higher frequency of burn injuries. On the other hand, we have relative scarcity of specialized burn care centers where the unfortunate victims of burn injuries can get the required level of professional burn care. Additionally, our nation is plagued by host of issues such as the lack of awareness on part of patients, lack of education, poverty, ignorance, lack of coordinated epidemiological data, poor- population with lack of access to specialized units, and hence suboptimal utilization of the existing burn care facilities. Owing to these formidable issues, burn care still continues to an unmet dream in Pakistan.1-4 Burn injuries are devastating that frequently cause significant morbidity, emotional distress, and a reduced quality of life. These injuries frequently require long-term treatment, including hospitalization, reconstructive surgical procedures, and frequent outpatient follow up visits. Burn injury victims as well as their families not only suffer economically but also take a significant psychosocial brunt of the misfortune. They may develop disabling post burn contractures, chronic non-healing wounds, and sometimes Marjolin’s Ulcers in their wounds. The management of these complications is even more difficult and expensive than the appropriate initial management of burn injuries in their acute phase. 5,6 Severe burn injuries require prompt, specialized treatment, and the demand for cellular and tissue-based products is increasing, particularly when there are limited donor sites for grafting tissue from uninjured skin areas.7 However, in Pakistan there is a shortage of burn centers, with existing centers lacking resources and located mainly in large urban centers. Consequently, treatment is delayed and both survival and recovery rates are lowered, and this gap in resources and infrastructure often leads to suboptimal patient outcomes.8,9 Peoples with lack of rehabilitation and psychological support, even many years after their first injury, many burn survivors continue to face physical and mental health difficulties. Numerous significant issues exacerbate this crisis. For initial reasons, there is a lack of preventive education on prevention of fire and burning risk, particularly in areas of poverty. A shortage of rules and regulations for the proper use of stoves with gas, burning materials, and industrial equipment increases the risk of accidental injuries. Acid attacks and the domestic violence also lead to deliberate burn injuries, resulting in a complicated combination of social and health problems that require immediate intervention. To overcome this disease, several different strategies has become important. Enhancing the number and breadth of burn care centers is a first step toward ensuring that medical care is available even in rural areas. Furthermore, adding burn preventive measures into public health campaigns could boost understanding of fundamental fire safety and first-aid procedures, while community education programs could assist minimize the number of both accidental and purposeful burn injuries. Healthcare workers proper training to recognize and properly manage burns, particularly in emergency situations, is also critical. Subsequently it is necessary to incorporate psychological counseling into burn care procedures, ensuring that survivors receive comprehensive treatment which includes physical as well as psychological healing. Robust acute management of the burn injuries, timely instituted surgical excision and resurfacing, physiotherapy and physical habilitation are all the stepping stones towards the early social reintegration of the unfortunate burn victims. All these facets of management demand for a coordinated team work via multidisciplinary approach. The acute care physician, confident surgeon, intensivist, anesthetist, nutritionist, specialist nursing staff, social nurses, and physiotherapist all constitute the multidisciplinary team who collective contribute to manage the patient. Given the magnitude of burn injuries in Pakistan, following recommendations constitute the way forward to address the menace of burn sin National perspective: At national level, we need to start a national burns prevention and awareness programme. It should promote education and raise public awareness of several burn prevention topics. National burn injury funds should be generated to ensure finances of the poor patients who suffer burn injuries. This will help to ensure that no one with burns is left untreated owing to lack of money. As we have a relatively higher frequency of electrical burn injuries in Pakistan, stringent occupational safety protocols should be in place especially for WAPDA workers. It should be made mandatory to provide all safety gadgets to these workers who are at high risk of sustaining burn injuries. These include special protective gloves, protective long shoes and safety masks etc. The transformers, meters and live wires should be well protected and inaccessible to the public, particularly children. Safety codes should be developed for the high-tension wires passing in residential areas. Power poles should be placed well away from roads and playgrounds, and rooftops, among other things. All residential and business sectors should have well-planned electrical codes in place. Safe home and safe kitchen initiatives should be launched. Awareness and public education about the risky places of home as well as the risky activities of children would help to curb the menace of pediatric burn injuries in Pakistan. Social reforms and justice should help to curtail the high incidence of suicidal burns particularly among our urban women. Collaboration and coordination are imperative for addressing the looming threat of burns. All public health personnels, nurses, doctors, paramedics, public health authorities, ulamas, social leaders and non-governmental organizations should promote healthy attitudes to reduce the incidence of burns, The law makers should legislate to ensure actualization of the aforementioned strategies